PERAN KEPEMIMPINAN PENDIDIKAN DALAM INOVASI DALAM PENGAJARAN - Saifullah; Tin Amalia Fitri; Fisman Bedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Innovation in teaching is one of the key elements that support the development of education worldwide. In the era of globalisation and rapid technological advancement, there is a need for effective and efficient teaching methods. According to a report from UNESCO (2020), around 90% of students in the world experience learning disruptions due to the COVID-19 pandemic, which emphasises the importance of innovation in facing educational challenges. Innovation in teaching includes not only the use of technology, but also new and creative pedagogical approaches that can increase student engagement. Visionary education leaders can create an enabling environment for innovation, inspire teachers to adopt new methods, and encourage collaboration among stakeholders. Specifically, this journal aims to: Identify the characteristics and types of effective leadership in the educational context, analyse the strategies that educational leaders can use to create an environment that supports innovation, explore the challenges faced by educational leaders in implementing innovation and how to overcome them, provide recommendations for educational leaders to improve innovation in teaching in schools. This research used a literature study method with a qualitative approach. Analysis was conducted by categorising information based on relevant themes. The integration of technology in educational leadership is an important step; by utilising technology effectively, educational leaders can create a more interactive and engaging learning environment for students. Through training and developing educational leaders, building collaboration networks and integrating technology, educational leaders can create an environment that supports innovation. The implications of the findings suggest the need for investment in educational leader training and the development of collaboration networks. Schools need to be encouraged to adopt technology in the teaching process and provide equitable access for all students.